2023
DOI: 10.1186/s12871-023-02063-7
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic effect of total intravenous anaesthesia with propofol versus inhalational anaesthesia for acute postoperative pain after hepatectomy: a randomized controlled trial

Abstract: Background Postoperative pain control can be challenging in patients undergoing hepatectomy. A previous retrospective study on hepatobiliary/ pancreatic surgeries showed better postoperative pain control in patients who received propofol TIVA. The aim of this study was to determine the analgesic effect of propofol TIVA for hepatectomy. This clinical study has been registered at ClinicalTrials.gov (NCT03597997). Methods A prospective randomized cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In a systematic review and meta-analysis on the impact of propofol on post-operative pain outcome. Wong et al 25 have reported that the use of propofol-based anesthesia can reduce postoperative pain scores and reduce opioid consumption after surgery. In another meta-analysis Peng et al, 15 concluded in a contrast way that none of the post-operative pain outcomes was significantly changed or improved using propofol instead of sevoflurane for maintenance of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review and meta-analysis on the impact of propofol on post-operative pain outcome. Wong et al 25 have reported that the use of propofol-based anesthesia can reduce postoperative pain scores and reduce opioid consumption after surgery. In another meta-analysis Peng et al, 15 concluded in a contrast way that none of the post-operative pain outcomes was significantly changed or improved using propofol instead of sevoflurane for maintenance of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of different anesthetic techniques such as propofol-based total intravenous versus inhalational anesthesia seems to be very limited, although theoretically helpful through the antagonizing effect of propofol on the N-methyl-D-aspartate (NMDA) receptor and possibly preventive in certain study populations [6,103,132]. While certain effects seem to make sense in a pathophysiological way and single studies show some effects of pharmacological interventions, a currently updated meta-analysis shows the disappointing fact that overall, the effects of most drugs (e.g.…”
Section: Risk Factors Related To Surgical Procedures and Pain Managementmentioning
confidence: 99%
“…Five clinical trials did not show a significant difference. 13 The use of bilateral tranversus abdominis plane block for abdominoplasty was associated with a longer postoperative analgesia duration in the last 24 hours and lower morphine consumption in the first 24 hours than other surgically infiltrated anesthetic techniques. 14 Liposomal bupivacaine (Exparel) was introduced as a safe method and an alternative to invasive postoperative pain management options such as PCA, epidurals, peripheral nerve catheters, or intravenous narcotics.…”
Section: Introductionmentioning
confidence: 97%